Mass Spectral Studies of Some 6-(5-Aryl-4,5-dihydropyrazol-3-yl)flavones and Chromones - PRABHA SHARMA, VINAY; V. SINGH, OM (Asian Journal of Chemistry, 2010)
Mass spectral fragmentation patterns of some 6-(5-aryl-4,5- dihydropyrazol-3-yl)flavones as well as chromones are being reported in present publication. Distinct pattern of fragmentation have been observed. These studies were carried out to provide additional support to the structures assigned to compounds.